2007
DOI: 10.1186/1742-4682-4-18
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous ion diffusion within skeletal muscle transverse tubule networks

Abstract: Background: Skeletal muscle fibres contain transverse tubular (t-tubule) networks that allow electrical signals to rapidly propagate into the fibre. These electrical signals are generated by the transport of ions across the t-tubule membranes and this can result in significant changes in ion concentrations within the t-tubules during muscle excitation. During periods of repeated highfrequency activation of skeletal muscle the t-tubule K + concentration is believed to increase significantly and diffusive K + tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…In our model, the slow diffusion zone can only exchange with the rapid diffusion zone at the distal end of the T-tubule farthest from the extracellular space. The equations are: c1false(x,tfalse)t=τCaDCa2c1false(x,tfalse)x2δfalse(xfalse)·kfalse(c1false(x,tfalse)c2false(tfalse)false)σc1·cEgoodbreakdN2false(tfalse)dt=kfalse(c1false(0,tfalse)c2false(tfalse)false)goodbreakcEfalse(x,tfalse)t=τEDE2cEfalse(x,tfalse)x2σc1·cE where k is the exchange rate between calcium in the slow and rapid diffusion zones, c 2 is the concentration of calcium in the slow diffusion zone (c 2 = N 2 /V 2 ), σ is a rate constant for Ca 2+ chelation by EGTA, D Ca 54 and D E 55 are the free diffusion constants of Ca 2+ and EGTA, respectively, and τ Ca and τ E are tortuosity factors for Ca 2+ and EGTA, respectively, that account for reduced diffusion in the T-tubule. The delta function, δ(x), indicates that compartment exchange only influences c 1 at the x = 0 end of the T-tubule.…”
Section: Methodsmentioning
confidence: 99%
“…In our model, the slow diffusion zone can only exchange with the rapid diffusion zone at the distal end of the T-tubule farthest from the extracellular space. The equations are: c1false(x,tfalse)t=τCaDCa2c1false(x,tfalse)x2δfalse(xfalse)·kfalse(c1false(x,tfalse)c2false(tfalse)false)σc1·cEgoodbreakdN2false(tfalse)dt=kfalse(c1false(0,tfalse)c2false(tfalse)false)goodbreakcEfalse(x,tfalse)t=τEDE2cEfalse(x,tfalse)x2σc1·cE where k is the exchange rate between calcium in the slow and rapid diffusion zones, c 2 is the concentration of calcium in the slow diffusion zone (c 2 = N 2 /V 2 ), σ is a rate constant for Ca 2+ chelation by EGTA, D Ca 54 and D E 55 are the free diffusion constants of Ca 2+ and EGTA, respectively, and τ Ca and τ E are tortuosity factors for Ca 2+ and EGTA, respectively, that account for reduced diffusion in the T-tubule. The delta function, δ(x), indicates that compartment exchange only influences c 1 at the x = 0 end of the T-tubule.…”
Section: Methodsmentioning
confidence: 99%
“…72 Several groups have shown that diffusion of extracellular potassium of skeletal muscle into systemic circulation is limited; the diffusion coefficient is less than 20% of its value in free solution. 73 …”
Section: Exercise and Potassium Homeostasismentioning
confidence: 99%
“…Transverse (T)-tubules; invaginations of the plasma membrane, allow this to occur uniformly across the whole cell (Brette and Orchard, 2003). This is made possible because (i) the T-tubules occur at ~2 μm intervals at approximately every z line and run deep into the interior of the cell, such that most sarcomeres are individually served by a singular T-tubule (Soeller and Cannell, 1999); (ii) sarcolemmal proteins that traffic ions across the plasma membrane are concentrated in the T-tubules (Brette and Orchard, 2003), and (iii) the T-tubules themselves constitute extracellular ion reservoirs that ensure a rapid access for transmembrane inward transport (Shorten and Soboleva, 2007; Swift et al, 2006). Thus, an intact network of T-tubules supports a rapid and coordinated contraction.…”
Section: Introductionmentioning
confidence: 99%